Characteristics of Tourists Visiting Setu Babakan - Dipa Awaloedin; Padri Achyarsyah; Rizki Nurul Nugraha; Muhammad Surya Saleh (West Science Information System and Technology, 2024)
The research with the title "Characteristics of Tourists Visiting Setu Babakan" was chosen to understand more deeply the characteristics of tourists visiting a tourist destination. The success and sustainability of a destination is highly dependent on a deep understanding of geography, demography, psychography and tourist behavior. The research location is Setu Babakan, Srengseng Sawah, Jagakarsa, South Jakarta. The urgency of this research is to improve the tourist experience and optimize the utilization of Setu Babakan's resources. By analyzing tourist characteristics, Setu Babakan can plan development strategies more effectively and can increase the number of visits. The data collection method is by distributing questionnaires to 100 respondents who have been determined by the slovin formula, interviews with informants who are purposely selected, and literature from previous studies. This type of research data is quantitative and the approach used is descriptive quantitative. The results showed that most Setu Babakan tourists came from within the city, dominated by Gen Z and Millennial age groups with preferences for cultural tourism activities. Setu Babakan tourists are relatively middle economic level, intend to visit again, and are willing to recommend this destination to friends and family. Setu Babakan needs to improve facilities in accordance with tourist expectations.